Natural Disaster, Migration, and Regional Development - Daisuke Ikazaki (European Regional Science Association (ERSA), 2015)
As described in this paper, a simple matching theory is constructed to ascertain how natural disasters affect regional economic activities and migration. Section 2 introduces a simple matching theory model based on previous studies. This theory explains how the unemployment rate, a measure of market tightness, the wage rate, and other important variables are determined. Section 3 describes integration of the elements of natural disasters into the model of section 2. Assuming that agglomeration increases productivity, then in a typical case, one can infer an inverted U-shaped relation between utility (Wu) and the regional population (L). When a natural disaster occurs, production factors are decreased, thereby reducing productivity. Consequently, people move from the affected areas to other cities: population drain occurs. Section 4 extends the model presented in section 3. In section 4.1, regional loyalty is considered. Damage caused by natural disasters decreases the utility of each household in the affected areas. However, presuming that the utility difference between the domicile (hometown) and other regions is low, then it seems likely that people will tend to remain in their hometown even if monetary gains could be made by migrating to other areas. Consequently, multiple steady states exist. In 4.2, we assume that productivity depends on public capital, which is degraded by a natural disaster.@Immediately following the natural disaster, people in the affected areas might migrate to other regions. The effects of fiscal policies to recover public capital are also discussed. Results show that once migration and a population drain occur, such fiscal policies might deteriorate the regional economy further: excess supply of public capital increases the onus of the region. Such reconstruction policies decrease the household utility. Fiscal policies might engender further population outflow.
Keywords: C78; Q54; R11; R23; 330; atural disaster; Migration; Matching theory; Regional economics